Reconfigurable Interdigital Bandpass Filter for wireless Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The new age wireless applications demand sharp rejection of unwanted signals at MHz frequencies. This necessitates the design of low loss, high attenuation bandpass filters. This paper proposes the design of reconfigurable interdigital bandpass filter for wireless applications using varactor diode tuning mechanism. An electronically tunable bandpass filter at 1.2GHz is designed and simulated using Advanced Design System (ADS)simulation tool from Keysight. The tuning is achieved by changing the biasing voltage from 0V to 9V of the varactor diode with the tuning range of 1GHz to 1.4GHz having a bandwidth of 200MHz and the insertion less than 3dB and the return loss is more than 10dB.